Supportive care needs and quality of life among cancer patients in China: A cross-sectional study - Bingshuang Wang; Xinyan Hu; Wanzhen Ding; Huimin Guo; Xiaoliang Ren (PLoS ONE, 2025)
Introduction In this study, the factors associated with unmet supportive care needs (SCNs) were examined, and their correlation with quality of life (QoL) among cancer patients was explored. Methods This cross-sectional study included 137 cancer patients who were recruited via convenience sampling from an oncology department at a tertiary cancer hospital in China. Three assessment instruments were employed herein: a general information questionnaire, the Chinese version of the Supportive Care Needs Survey short form (SCNS-SF34-C), and the functional subscale of the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire-Core 30 (EORTC QLQ-C30). Results Among the five domains of the SCNS-SF34-C, the health system and information domain had the highest mean score (M = 2.74; SD = 0.75), followed by the psychological domain (M = 2.36; SD = 0.85). Five factors were associated with the unmet SCNs of cancer patients: sex, educational background, disease awareness, smoking status, and drinking habits (all p < 0.05). Moreover, participants with unmet psychological, physical and daily living needs had significantly lower QoL scores in all functional and symptom domains (all p < 0.05). Conclusions Chinese cancer patients face notable unmet needs in the health system and information domain. Future studies should focus on designing individualized interventions to improve supportive care among cancer patients and to enhance their QoL.